2002
DOI: 10.1021/es011054r
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Poly(methylene)-Rich Amorphous Aliphatic Domains in Humic Substances with Sorption of a Nonpolar Organic Contaminant, Phenanthrene

Abstract: The structural makeup of natural organic matter plays a major role in regulating its capacity to retain nonionic hydrophobic organic compounds (HOCs). We used a model HOC--phenanthrene--to investigate the correlations between sorption capacity, specifically the modified Freundlich coefficient (K'f), and compositional data of humic acids, humins, and a peat obtained from quantitative 13C solid-state NMR spectroscopy. A positive correlation between K'f and the weight fraction of amorphous poly(methylene) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
132
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 25 publications
17
132
1
1
Order By: Relevance
“…Previous study reported negative relationship between paraffinic carbon contents and (O + N)/C, which suggests that high paraffinic carbon contents would often be associated with low polarity in a sorbent (Chen et al, 2005). Significant positive correlation was also reported between K OC values of Phen and paraffinic carbon content (Chefetz et al, 2000;Mao et al, 2002;Salloum et al, 2002). Moreover, as the NHC fraction isolated in this study for the Porphyra samples contains higher polymethylene carbon than that for the Seaweed or Spirulina, it exhibits higher biosorption capacity.…”
Section: Correlation Between Biosorption Isotherm Parameters and Propsupporting
confidence: 49%
“…Previous study reported negative relationship between paraffinic carbon contents and (O + N)/C, which suggests that high paraffinic carbon contents would often be associated with low polarity in a sorbent (Chen et al, 2005). Significant positive correlation was also reported between K OC values of Phen and paraffinic carbon content (Chefetz et al, 2000;Mao et al, 2002;Salloum et al, 2002). Moreover, as the NHC fraction isolated in this study for the Porphyra samples contains higher polymethylene carbon than that for the Seaweed or Spirulina, it exhibits higher biosorption capacity.…”
Section: Correlation Between Biosorption Isotherm Parameters and Propsupporting
confidence: 49%
“…Similar to humic substances, that have a different sorption (by partition) capacity, correlated with the content of amorphous poly-(methylene) structures, but poorly correlated with polarity and aromaticity indices (Mao et al, 2002), the sorption of polar and nonpolar aromatic contaminants by biochar occurs by different mechanisms (partition and adsorption), each with specific transitions (Chen et al, 2008).…”
Section: Characterization Of Biocharmentioning
confidence: 99%
“…2), a peak at 1720 cm − 1 (-COOH) was observed, but the -COOH peak in the 13 C NMR spectra of 165-190 ppm was very weak. Mao et al (2002) reported that the sp 2 carbons (110-220 ppm) or -COOH tend to be underrepresented by CP MAS 13 C NMR due to their longer relaxation times (T 1 , spin-lattice relaxation time). According to this observation, -COOH of the lipid may be in rigid domains, corresponding to longer T 1 Mao et al, 2000).…”
Section: Tablementioning
confidence: 99%